Rethinking Motivation and Reward Management: What We Know and Do not Know - Wang, Zheni (Edward Elgar Publishing Ltd., 2025)
This innovative book examines the controversial relationship between motivation and rewards from multiple theoretical and practical perspectives. It analyzes cutting-edge research on work motivation and reward management's economic and psychological roots and identifies future directions for advancement in the field. © Zheni Wang 2025.
Keywords: Compensation And Benefits; Motivation At Work; Reward Management; Self-Regulations; Total Rewards; Work Engagement; dept.mgt

From fragmentation to integration: finding the psychological and instrumental common ground for algorithmic management and marketing - Wang, Zheni; Wang, Emma; Zhu, Guorong (SSRN Electronic Journal, 2026)
Keywords: Common ground; Corporate governance; Fragmentation (computing); Service (business); Spillover effect; Stakeholder; Stakeholder analysis; Stakeholder theory; dept.mgt; dept.mrk

Understand the Changes in Motivation at Work: Empirical Studies Using Self-Determination Theory-Based Interventions - Wang, Zheni; Briand, Mélanie (Behavioral Sciences, 2025)
Managers often need to stay motivated and effectively motivate others. Therefore, they should rely on evidence-based interventions to effectively motivate and self-motivate. This research investigated how self-determination theory-based interventions affect employees' motivation dynamics and motivational consequences within short time frames (i.e., within an hour, within a few weeks or months) in two empirical studies. Study one focused on assessing the effectiveness of a one-day training workshop in helping to improve managers' work motivation, basic psychological needs satisfaction/frustration, subordinates' motivation, and perceptions of managers' needs-supportive/thwarting behaviors within a few weeks. Results support the effectiveness of the training, as managers were rated by their direct subordinates as having fewer needs-thwarting behaviors and reported self-improvement in needs satisfaction and frustration six weeks after completing the training program. Study two used the mean and covariance structure analysis and tested the impact of three types of basic psychological needs-supportive/thwarting and control conditions (3 × 2 × 1 factorial design) on participants' situational motivation, vitality, and general self-efficacy for playing online word games within 30 min. Multi-group confirmatory factor analysis (CFA) confirmed the scalar measurement invariance, then latent group mean comparison results show consistently lower controlled motivation across the experimental conditions. During a quick online working scenario, the theory-based momentary intervention effectively changed situational extrinsic self-regulation in participants. Supplementary structural equation modeling (SEM; cross-sectional) analyses using experience samples supported the indirect dual-path model from basic needs satisfaction to vitality and general efficacy via situational motivation. We discussed the theoretical implications of the temporal properties of work motivation, the practical implications for employee training, and the limitations.
Keywords: Applied psychology; Autonomy; Computer science; Confirmatory factor analysis; Psychological intervention; Psychology; Self-determination theory; Situational ethics; Social psychology; Structural equation modeling; Work (physics); Work motivation; dept.mgt; employee training and development; motivation change; self-determination theory; theory-based interventions

Thriving in the dynamics: a multi-level investigation of needs-supportive features, situational motivation, and employees’ subjective well-being - Wang, Zheni; Panaccio, Alexandra (Current Psychology, 2023)
Employees often demonstrate various regulatory intentions toward multiple responsibilities they must fulfill on the job. Therefore, it is possible that employees’ motivation changes during the workday because of the various situations they have experienced and that these motivational fluctuations affect their subjective well-being across different activities. Following the integrated frameworks of the self-determination theory (SDT) and the hierarchical model of motivation (H-SDT), the present research studied the variations of employees’ daily motivation for work across different activities using the survey of day reconstruction method (DRM). Multi-level structural equation modeling (MSEM) was used to analyze the variations in the perceived three basic psychological (i.e., autonomy-, relatedness-, and competence-) needs-supportive features (NSFs), situational motivation, and variables capturing the employees’ subjective well-being (including vitality and positive/negative affect) laid out according to a list of work episodes in DRM. Results of this study confirmed that employees’ subjective well-being (mainly vitality and positive affect) were positively promoted by NSFs pertained to specific work activities via the indirect path of situational autonomous motivation at work. Furthermore, vitality and positive affect were also directly predicted by situational autonomous motivation. These empirical findings expanded the research evidence supporting employees’ subjective well-being as a multi-level and multi-dimensional dynamic motivational consequence promoted by configurable specific NSFs at work. We also discussed the limitations and future directions for this line of research.
Keywords: Dynamics of work motivation; Multi-level modeling; Psychological health; dept.mgt; peer-reviewed

A Longitudinal Investigation of the Changes in Work Motivation and Employees’ Psychological Health - Wang, Zheni; Panaccio, Alexandra (Administrative Sciences, 2022)
Organizations strive to motivate employees to thrive at work. However, employees’ motivation is likely to vary over a short period (e.g., a few months) to cope with the routine dynamics of organizations’ activities. These motivation dynamics covary with employees’ affective, cognitive, and behavioral outcomes in the workplace. Moreover, employees’ psychological health, a multidimensional concept focused on the individual’s well/ill-being simultaneously, changes over time. Using the integrated theoretical frameworks of self-determination theory (SDT) and the hierarchical model of self-determined motivation (H-SDT), this research sought to examine the motivational changes following the dual-path model. In particular, this work sought to unpack the temporal dynamics in employees’ subjective well/ill-beings predicted by the changes in basic needs satisfaction/frustration through autonomous/controlled motivation, while considering the characteristics of people’s general causality orientations (trait-level motivation). Over four months, longitudinal field data were collected from the employees in several private small businesses in the consumer product retail industry. Latent growth modeling (LGM) results supported the positive dual relations between the changes in employees’ psychological health and basic psychological needs satisfaction/frustration, but neither the changes of autonomous/controlled work motivation nor the indirect change paths via autonomous/controlled work motivation were significant. Finally, we discussed the theoretical and practical implications of the findings. Limitations and possible future research directions to further this line of research on the dynamic of work motivation were also summarized.
0 citations (Crossref) [2023-10-31] Number: 4
Keywords: change in motivation; dept.mgt; longitudinal study; peer-reviewed; psychological health

Understand the changes in motivation: comparative studies using theory-based interventions - Wang, Zheni; Briand, Melanie (Academy of Management Proceedings, 2023)
Managers often need to stay motivated and effectively motivate others. Therefore, they should rely on evidence-based interventions to manage the daily routine of motivational dynamics at work. This research answered how self-determination-theory-based interventions change employees’ motivation and motivational consequences during short time frames (i.e., within an hour, within a few weeks/months). Field study one focused on assessing the effectiveness of a one-day training workshop in helping improve managers’ work motivation, basic psychological needs satisfaction/frustration, and changing managers’ needs-supportive/thwarting behaviors within a few weeks. Results supported the training effectiveness as managers were rated less needs-thwarting by their direct subordinates and self-reported improvement in needs satisfaction/frustration six weeks after completing the training program. Online study two used the mean and covariance structure analysis and tested the three types of basic psychological needs supportive/thwarting and control conditions (3x2x1 factorial design) on the situational motivation, vitality, and general self-efficacy for playing online word games within 30 minutes. Multi-group confirmatory factor analysis (CFA) confirmed the scalar measurement invariance, then latent group means comparison results showed consistently lower controlled motivation across the needs-supportive and thwarting experimental conditions. During a quick online working scenario, the theory-based momentary intervention effectively changed situational extrinsic self-regulation in Amazon MTurk participants. Supplementary structural equation modeling (SEM) analyses using experience samples supported the indirect dual-path model from basic needs satisfaction to vitality and general efficacy via situational motivation. We discussed the theoretical implications of the temporal properties of work motivation, the practical implications on employee training and organizational change programs, and the limitations.
Keywords: AOM Annual Meeting Proceedings 2023; AOM Boston 2023; Organizational Behavior; dept.mgt

A Chinese–Canadian Cross-Cultural Investigation of Transformational Leadership, Autonomous Motivation, and Collectivistic Value - Wang, Zheni; Gagné, Marylène (Journal of Leadership & Organizational Studies, 2013)
Synthesizing theories of transformational leadership and self-determination, this research investigated whether transformational leaders (a) promote the autonomous motivation of their subordinates and whether (b) it results in higher autonomous motivation when subordinates hold high collectivistic values. Multilevel data were obtained from work samples in China and Canada. The results showed a positive relation between managers’ transformational leadership and subordinates’ autonomous motivation cross-culturally. Although higher collectivistic values were related to higher autonomous motivation, collectivist values did not significantly moderate the motivational effect of transformational leadership.
Keywords: dept.mgt; peer-reviewed

A temporal analysis of employees’ situational work motivation and well- being - Wang, Zheni; Panaccio, Alexandra Joelle (Academy of Management Proceedings, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: dept.mgt

Developing entrepreneurship competence in STEM graduate students through a fellowship model - Wang, Zheni; Daneshmandi, Leila; Christodoulidou, Andri (Academy of Management Proceedings, 2025)
Keywords: Cognition; Competence (human resources); Entrepreneurship; Entrepreneurship education; Graduate students; Higher education; Mindset; Qualitative research; Value (mathematics); dept.mgt

A Self-Determination Approach to Understanding Individual Values as an Interaction Condition on Employees' Innovative Work Behavior in the High-Tech Industry - Wang, Zheni; Gao, Mengchan; Panaccio, Alexandra (Journal of Creative Behavior, 2021)
Drawing on self-determination theory (SDT; E.L. Deci & R.M. Ryan, 1985, 2000) and using corporate samples (N = 284; 63% Male; Mean Age = 34, SD = 6.09) from high-tech firms in China, this empirical study explored the path model from satisfaction of the basic psychological needs for autonomy, competence, and relatedness, through autonomous motivation to employees' innovative work behavior (“IWB”; J. De Jong & D. Den Hartog, 2010). It also simultaneously examined the interactions between autonomous work motivation and individual values (collectivism, H.C. Triandis (1995); uncertainty avoidance, R. J. House, P. J. Hanges, M. Javidan, P. W. Dorfman, & V. Gupta (2004); and power distance, J. Farh, R.D. Hackett, & J. Liang (2007)) in the conditioned path model. The regression results obtained from conditional PROCESS analysis (A.F. Hayes, 2013, 2018) suggest that basic psychological needs satisfaction is positively related to employees' IWB via autonomous motivation, but that these indirect effects were weaker when employees' power distance value orientation was high. Implications, limitations, and future research directions are discussed. © 2020 by the Creative Education Foundation, Inc.
14 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85082766274
Keywords: dept.mgt; peer-reviewed

Servant leadership and employee outcomes: the moderating role of subordinates’ motives - Donia, Magda B.L.; Raja, Usman; Panaccio, Alexandra; Wang, Zheni (European Journal of Work and Organizational Psychology, 2016)
Drawing from implicit leadership theories we advance servant leadership theory by examining moderating mechanisms that explain under what conditions servant leader behaviours impact followers in organizations. Specifically, we focused on the moderating role of subordinates’ motivational orientations—prosocial values or impression management motives—in relationships between servant leadership behaviours and job satisfaction, as well as subordinate organizational citizenship behaviours (OCBs). Using time-lagged data collected from 192 supervisor-subordinate dyads, we found that servant leadership was positively associated with employees’ job satisfaction, but not significantly related to their performance of OCBs. We also found evidence that subordinates’ motives moderate the relationships between servant leadership and outcomes. Specifically, employees high on impression management experienced lower levels of job satisfaction than their lower scoring counterparts. Our findings suggest that servant leadership may not be equally beneficial for all followers. We discuss implications for theory and practice.
_eprint: https://doi.org/10.1080/1359432X.2016.1149471
Keywords: citizenship behaviours; dept.mgt; employee motives; implicit leadership theories; job satisfaction; peer-reviewed; servant leadership

Building positive experiences for sustainable development - Wang, Zheni; Zhu, Guorong; Zhang, Mengyi; Wang, Emma; Lv, Shuangning; Zheng, Jiawei; Shen, Yan; Steckler, Erica (Academy of Management Proceedings, 2025)
Keywords: Creativity; Face (sociological concept); Grounded theory; Stakeholder; Stakeholder engagement; Sustainability; Sustainable development; Work (physics); dept.mgt; dept.mrk

Servant leadership and employee wellbeing: A crosscultural investigation of the moderated path model in Canada, Pakistan, China, the US, and Brazil - Wang, Zheni; Panaccio, Alexandra; Raja, Usman; Donia, Magda; Landry, Guylaine; Pereira, Michelle Morelo; Ferreira, Maria Cristina (International Journal of Cross Cultural Management, 2022)
Drawing on samples from Canada, Pakistan, China, the US, and Brazil comprising over 800 employees, we examined whether servant leaders (SL) - characterized as putting the needs of others above their own - promote employees’ well-being via autonomous motivation, accounting for employees’ power distance and collectivism values as moderating variables. Autonomous motivation, a type of self-regulation, sustains one’s well-being. Personal values facilitate one’s work behaviors cross-culturally. Multigroup confirmatory factor analysis (CFA) results confirmed matrix invariance of all the measures. The path and moderation analyses result using multilevel structural equation modeling (SEM) supported the positive direct and indirect paths among SL, autonomous motivation, and psychological well-being across the five cultures; Collectivistic value negatively moderated the relationship between servant leadership and autonomous motivation across the Chinese and US samples. In addition, with only a limited number of items, measurements of SL and vitality achieved scalar invariance. ANOVA test results also confirmed the significant comparative differences in these two variables among the cultural groups. Findings in this research provided robust and empirical support for the motivational effects of the servant leadership theory across the globe. Theoretical and practical implications for evidence-based cross-cultural management practices and future directions for leadership training in diverse cultural contexts are discussed.
0 citations (Crossref) [2023-10-31]
Keywords: Servant leadership; autonomous motivation; dept.mgt; peer-reviewed; personal values; psychological well-being

The Multidimensional Work Motivation Scale: Validation evidence in seven languages and nine countries - Gagné, Marylène; Forest, Jacques; Vansteenkiste, Maarten; Crevier-Braud, Laurence; van den Broeck, Anja; Aspeli, Ann Kristin; Bellerose, Jenny; Benabou, Charles; Chemolli, Emanuela; Güntert, Stefan Tomas; Halvari, Hallgeir; Indiyastuti, Devani Laksmi; et al. (European Journal of Work and Organizational Psychology, 2015)
Self-determination theory proposes a multidimensional conceptualization of motivation comprising autonomous and controlled forms. Whereas autonomous motivation relates positively to individuals’ optimal functioning (e.g., well-being, performance), controlled motivation is less beneficial. To be able to use self-determination theory in the field of organizational behaviour, the Multidimensional Work Motivation Scale was developed and tested using data from 3435 workers in seven languages and nine countries. Factorial analyses indicated that the 19-item scale has the same factor structure across the seven languages. Convergent and discriminant validity tests across the countries also indicate that the psychological needs for autonomy, competence, and relatedness as well as the theoretically derived antecedents to work motivation (e.g., leadership and job design) are predictably related to the different forms of motivation, which in turn are predictably related to important work outcomes (e.g., well-being, commitment, performance, and turnover intentions). Implications for the development of organizational research based on self-determination theory are discussed.
_eprint: https://doi.org/10.1080/1359432X.2013.877892
Keywords: Autonomous motivation; Controlled motivation; Cross-cultural; Extrinsic motivation; Intrinsic motivation; Self-determination theory; Validation; Work motivation; dept.mgt